Analisis Perbandingan Kinerja Keuangan Perusahaan Sebelum Dan Setelah Akuisisi (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022) - Maulina, Argita Sara; Rauf, Anwar; Nurman, Nurman; Ramli, Anwar; Burhanuddin, Burhanuddin (J-MAS (Jurnal Manajemen dan Sains), 2024)
This research is to find out whether there are significant differences in the company's financial performance before and after carrying out acquisition activities. This research involves manufacturing companies listed on the Indonesian Stock Exchange and recorded as having made acquisitions in the last five year period (2018-2023). This research is quantitative research using a population of 159 companies and producing a sample of 20 manufacturing companies that have made acquisitions in the last five years (2018-2022) and are listed on the Indonesian Stock Exchange. The hypothesis test in this research is using the paired sample t test method, from The results obtained were five hypotheses, namely 3 hypotheses were rejected while the other 2 hypotheses were accepted, where the Current Ratio variable as H1, the Quick Ratio variable as H2 and the Total Asset Turnover variable as H4 did not have a significant difference in the financial statements before and after the acquisition while the Debt to Equity variable The ratio as H3 and the Net Profit Margin variable as H5 have significant differences in the financial statements before and after carrying out acquisition activities.